The Influence of Office Technology and Job Performance of Office Professionals as Mediated by Interpersonal Skills - Lowena G. De Ocampo; Lualhati P. Sausa; Jolly S. Balila; Glenda Joy B. Lopez; Reuel E. Narbarte; Ruben T. Carpizo, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Office professionals are integral members of the organization who utilize office technology provided by the organization to produce an outstanding performance. However, office professionals face the challenges on adequacy, knowledge, and skills related to office technology. The paper investigated the relationship of office technology and job performance of office professionals as mediated by interpersonal skills. Data from 320 office professionals were collected through convenience sampling from selected higher education institutions (HEIs) in the Philippines. This descriptive-correlational study utilized a self-constructed and validated questionnaire. The statistical analyses were performed using the SPSS and Smart PLS. Results revealed that technological equipment in the workplace were available and adequate. Furthermore, the office professionals are moderately knowledgeable on how to use the office technology. The extent of interpersonal skills in terms of workplace communication are very good, the respondents’ motivation is high, and their teamwork skills is good. Adequacy of office technology and knowledge are significantly related with the subdimensions of interpersonal skills. Office technology and interpersonal skills are positively correlated with the job performance of the respondents. The mediation analysis revealed that the direct and indirect effects of office technology on job performance is significant as mediated by interpersonal skills. These imply that adequacy, availability, knowledge, and usage treated as whole can improve the job performance of office professionals, however, it is partially mediated by the interpersonal skills. Both office technology and interpersonal skills can improve the job performance of office professionals with a medium effect size (f2) of 0.245. Recommendations are proposed to office professionals and HEIs in general to enhance the knowledge and skills of office professionals and their actual office practices in organizations for organizational productivity and success.